PERANAN PDRB SUB-SEKTOR PERKEBUNAN TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN BOLAANG MONGONDOW - Wanda Wulandari; Celsius Talumingan; Caroline B.D. Pakasi; Ribka Kumaat (COCOS, 2015)
ABSTRACT This studyaimed toanalyzethe role ofGDPPlantationsub-sector to economic growthin BolaangMongondow. Data collection is donefor 3months fromJanuary toMarch 2015. The data usedin this research issecondary data, the datais takenfrom relevant agencies that is; The Central Statistics Agency Bolaang Mongondow, BAPPEDA Bolaang Mongondow Regency, Department of Agriculture and Livestockin BolaangMongondow, and Department of Forestry and Plantationin BolaangMongondow. The results showed thatContributions GNP Plantation Sub-Sector to economic growth in Bolaang Mongondow is accelerating as shown by the economic growth of GNP on the constant prices in figures 2014, where in 2013 reach 6,84 % from the previous year to reach 6,49 %. Plantation sub-sector ia a sector base value of Location Quotient (LQ) average of 1,10 can move the economy in Bolaang Mongondow. Keywords : GNP, Plantation Sub-Sector, Economic growth